Enrolling a rural community pharmacy as a Vaccines for Children provider to increase HPV vaccination: a feasibility study - Casey L. Daniel; Frances Lawson; Macy Vickers; Chelsea Green; Anna Wright; Tamera Coyne-Beasley; Hee Y. Lee; Stacie Turberville (BMC, 2021)
Abstract Background Human papillomavirus (HPV) is the most common sexually transmitted infection in the U.S. with over 80 million infected individuals. High-risk strains are associated with 6 different cancers. Although infection is preventable, U.S. vaccination rates remain suboptimal and there are noted disparities between urban and rural communities due to economic barriers, lack of access, and low awareness and education. Methods The current pilot study sought to overcome these barriers through an interprofessional collaborative enrolling a community pharmacy in a rural, medically underserved Alabama county as a Vaccines for Children (VFC) provider to provide free vaccines to eligible adolescents. Program evaluation was conducted to determine the intervention's feasibility. Potential efficacy was assessed by analyzing county-level HPV vaccination uptake and completion rates using state immunization registry data. Results Over the 8-month study, 166 total vaccines were administered to 89 adolescents ages 10-18, including 55 doses of HPV vaccine, 53 doses of Tdap vaccine, 45 doses of meningococcal vaccine, and 13 doses of influenza vaccine. Among these adolescents, mean age was 12.6 years old, and 64 (71.9%) were VFC patients. The pharmacy recorded an increase in total vaccine administration of 158.8%, an increase in prescription revenue of 34.8%, and an increase in total revenue by 24.4% during the course of the study, compared to the previous year. Conclusions Findings from the current work demonstrate the potential of this strategy and can serve as a blueprint for statewide and national dissemination and implementation to ultimately increase access to vaccination services, increase vaccination rates, and reduce urban-rural vaccine disparities.